Economics as religion : from Samuelson to Chicago and beyond - Nelson, Robert H. (Robert Henry), 1944- (Pennsylvania State University Press, 2001)
In this study, Robert H. Nelson explores the genesis, the prophets, the prophesies, and the tenets of what he sees as a religion of economics that has come into full blossom in latter-day America. Nelson does not see "theology" as a bad word, and his examination of the theology underlying Samuelsonian and Chicagoan economics is not a put-down. It is a way of seeing the rhetoric of fundamental belief-what has been called "vision."